ANALYSIS OF SOCIAL RESPONSIBILITY IMPLEMENTATION OF PT SEMEN PADANG BASED ON THE LEVEL OF COMMUNITY SATISFACTION WITH THE CORPORATE IMAGE IN PADANG CITY - Satrio Rian Bhakti; Syukri Lukman; Harif Amali (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The beginning of the formation of social responsibility or better known as Corporate Social Responsibility (CSR) is the provision of assistance to local organizations and lower-class communities in developing countries from companies operating in the vicinity. This study is intended to analyze the relationship between CSR Implementation on Community Satisfaction and Corporate Image. This research will use quantitative methods. Based on the research objectives, it was made to analyze the Implementation of PT Semen Padang's Social Responsibility based on the Level of Public Satisfaction with the Company's Image in the City of Padang. The number of samples in this study were 130 samples. The results of this study are the implementation of CSR has an effect on the level of community satisfaction. The implementation of CSR has an effect on corporate image, the level of community satisfaction has an effect on corporate image. The implementation of CSR affects the Company's Image through Community Satisfaction.